Vaginal Mucosal Homeostatic Response May Determine Pregnancy Outcome in Women With Bacterial Vaginosis: A Pilot Study. Issue 5 (February 2016) - Faure, Emmanuel; Faure, Karine; Figeac, Martin; Kipnis, Eric; Grandjean, Teddy; Dubucquoi, Sylvain; Villenet, Céline; Grandbastien, Bruno; Brabant, Gilles; Subtil, Damien; Dessein, Rodrigue
Abstract : Abstract: Bacterial vaginosis (BV) is considered as a trigger for an inflammatory response that could promote adverse pregnancy outcome (APO). We hypothesized that BV-related inflammation could be counterbalanced by anti-inflammatory and mucosal homeostatic responses that could participate in pregnancy outcomes. A total of 402 vaginal self-samples from pregnant women in their first trimester were screened by Nugent score. In this population, we enrolled 23 pregnant women with BV but without APO, 5 pregnant women with BV and developing APO, 21 pregnant women with intermediate flora, and 28 random control samples from pregnant women without BV or APO. BV without APO in pregnant women was associated with 28-fold interleukin-8, 5-fold interleukin-10, and 40-fold interleukin-22 increases in expression compared to controls. BV associated with APO in pregnant women shared 4-fold increase in tumor necrosis factor, 100-fold decrease in interleukin-10, and no variation in interleukin-22 expressions compared to controls. Next-generation sequencing of vaginal microbiota revealed a shift from obligate anaerobic bacteria dominance in BV without APO pregnant women to Lactobacillus dominance microbiota in BV with APO. Our results show that the anti-inflammatory and mucosal homeostatic responses to BV may determine outcome of pregnancy in the setting of BV possibly through effects on the vaginal microbiota.